Effect of Feed Substrate Thickness on the Bandwidth and Radiation Characteristics of an Aperture-Coupled Microstrip Antenna with a High Permittivity Feed Substrate - Jae-Hyun Kim; Boo-Gyoun Kim (Journal of the Korean Institute of Electromagnetic Engineering and Science, 2018)
The impedance bandwidth and radiation characteristics of an aperture-coupled microstrip line-fed patch antenna (ACMPA) with a high permittivity (ɛr = 10) feed substrate suitable for integration with a monolithic microwave integrated circuit (MMIC) are investigated for various feed substrate thicknesses through an experiment and computer simulation. The impedance bandwidth of an ACMPA with a high permittivity feed substrate increases as the feed substrate thickness decreases. Furthermore, the front-to-back ratio of an ACMPA with a high permittivity feed substrate increases and the cross-polarization level decreases as the feed substrate thickness decreases. As the impedance bandwidth of an ACMPA with a high permittivity feed substrate increases and its radiation characteristics improve as the feed substrate thickness decreases, the ACMPA configuration becomes suitable for integration with an MMIC.